2019
DOI: 10.1038/s41372-019-0415-9
|View full text |Cite
|
Sign up to set email alerts
|

Medication use in infants with severe bronchopulmonary dysplasia admitted to United States children’s hospitals

Abstract: Objective: To identify the number of cumulative medication exposures and most frequently used medications in infants with severe BPD. Study Design: We performed a retrospective cohort study in infants with severe BPD admitted to United States children’s hospitals. We measured cumulative medication exposures in individual subjects and between-center variation after adjustment for infant characteristics. We then identified the specific medications and therapeutic classes with the highest rates of use. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…Compared with our findings of 48% of severe BPD patients receiving an IB, Bamat et al, using the PHIS database to study cumulative medicine exposures in severe BPD patients between 2007 and 2016, found that 38% of infants with severe BPD were exposed to albuterol [17]. Similar to our results, another study demonstrated significant variability in IB use, showing that the point SGA small for gestational age, IVH intraventricular hemorrhage, PDA patent ductus arteriosus.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Compared with our findings of 48% of severe BPD patients receiving an IB, Bamat et al, using the PHIS database to study cumulative medicine exposures in severe BPD patients between 2007 and 2016, found that 38% of infants with severe BPD were exposed to albuterol [17]. Similar to our results, another study demonstrated significant variability in IB use, showing that the point SGA small for gestational age, IVH intraventricular hemorrhage, PDA patent ductus arteriosus.…”
Section: Discussionsupporting
confidence: 84%
“…The paucity of data surrounding the indications, timing of use, and effectiveness of IBs in managing symptoms of BPD, as well as concerns for adverse effects, have likely led to the wide variation in IB exposure in infants with developing or established BPD [11,17]. For those with BPD, and especially severe BPD, the extent of IB use and the factors related to IB use are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The PROP study demonstrated the importance of contemporary diagnostic criteria and definitions for BPD . There is an equally compelling need to evaluate the effectiveness of commonly used medications for respiratory conditions in the NICU, ideally through robust randomized clinical trials . Well‐defined dosing criteria and risk/benefit evaluation are necessary for well‐designed trials.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, controlled trials are urgently needed for examining the use of both inhaled and oral medications in this high-risk populations. 15 17 …”
Section: Discussionmentioning
confidence: 99%